2017
DOI: 10.3389/fcimb.2017.00491
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Ergosterol in Berberine Tolerance Underlies Synergism of Fluconazole and Berberine against Fluconazole-Resistant Candida albicans Isolates

Abstract: Candida albicans is one of the most common fungal pathogens. Our previous study demonstrated that concomitant use of berberine (BBR) and fluconazole (FLC) showed a synergistic action against FLC-resistant C. albicans in vitro and BBR had a major antifungal effect in the synergism, while FLC played a role of increasing the intracellular BBR concentration. Since the antifungal activity of BBR alone is very weak (MIC > 128 μg/mL), it was assumed that FLC-resistant C. albicans was naturally tolerant to BBR, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…This result in agreement with the observation made by Ahmad et al (2010) wherein ergosterol synthesis was inhibited in C. albicans by eugenol and methyl eugenol in a dose dependent manner. Conversely, Xu et al (2017) have reported that the berberine treatment in fluconazole-resistant C. albicans increased the ergosterol content and up regulated the genes involved in ergosterol biosynthesis.…”
Section: Discussionmentioning
confidence: 95%
“…This result in agreement with the observation made by Ahmad et al (2010) wherein ergosterol synthesis was inhibited in C. albicans by eugenol and methyl eugenol in a dose dependent manner. Conversely, Xu et al (2017) have reported that the berberine treatment in fluconazole-resistant C. albicans increased the ergosterol content and up regulated the genes involved in ergosterol biosynthesis.…”
Section: Discussionmentioning
confidence: 95%
“…qRT-PCR was carried out on the QuantStudio ® 3 real-time PCR System (Applied Biosystems). Primers used in this study referred to Yi et al (2017) and were listed in Supplementary Table 1. The relative expression levels of target genes were calculated by the 2 −ΔΔ CT method (Livak and Schmittgen, 2001; Rybak et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Such similar synergistic phenomenon has been reported on palmatine, berberine, and calcium channel blockers. 17 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Growth curve assay was used to dynamically monitor the synergistic effect of PAB with FLC against planktonic C. tropicalis isolates. 17 The fungal supernatant (10 3 CFU/mL) containing agents (1 µg/mL PAB, 2 µg/mL FLC, and 1µg/mL PAB + 2µg/mL FLC) was grown with constant shaking at 37 ◦ C. The control was free of FLC and PAB. At designated time points (0, 12, 24, 48 h), the cell broths were pipetted out to determine the OD with microplate reader at 495 nm.…”
Section: Methodsmentioning
confidence: 99%